Multiparametric MRI for prostate cancer detection: Performance in patients with prostate‐specific antigen values between 2.5 and 10 ng/mL. Issue 5 (4th November 2013) - Petrillo, Antonella; Fusco, Roberta; Setola, Sergio V.; Ronza, Francesco M.; Granata, Vincenza; Petrillo, Mario; Carone, Guglielmo; Sansone, Mario; Franco, Renato; Fulciniti, Franco; Perdonà, Sisto
Abstract : Purpose: To assess the diagnostic performance of multiparametric MRI (mpMRI), in the detection of prostate cancer, including morphologic sequences (mMRI), diffusion‐weighted imaging (DWI), and MR spectroscopy (MRS). Combined morphological and functional MRI scoring systems was used for urological–radiological work‐up of patients with a prostate‐specific antigen (PSA) value ≤ 10 ng/mL. Materials and Methods: The study included 136 of 200 consecutive patients with PSA values between 2.5 and 4 ng/mL and an abnormal digital rectal examination (DRE), or patients with PSA values between 4 and 10 ng/mL, independently from DRE. Each patient provided informed consent to undergo at serum free/total PSA ratio (f/t PSA) assay, mMRI, MRS, DWI, and transrectal ultrasonography (TRUS) biopsy. The MRI datasets were scored singularly; then mMRI and DWI, mMRI and MRS data were combined in a coupled score, and finally mMRI, DWI, and MRS data were combined in a single score (cMRI score). Results: Scores were correlated to negative biopsies and significant/insignificant Gleason score biopsies. Receiver‐operator‐characteristic curve and McNemar tests were performed. Cancer was diagnosed in 18% of patients. The cMRI score showed: (i) the highest sensitivity (0.84) and negative predictive value (0.93); (ii) a significant correlation with Gleason score; and (iii) a statistically different median value between significant and insignificant Gleason score. Conclusion: The cMRI score could identify patients with a PSA≤10 ng/mL who will have a negative work‐up, for its high negative predictive value, and patients at high risk for significant prostate cancer because of its correlation with the Gleason score.J. Magn. Reson. Imaging 2014;39:1206–1212 . ©2013 Wiley Periodicals, Inc .